A tale of FTKMA focus groups - Azizuddin, Abd Aziz (Faculty of Mechanical & Automotive Engineering Technology, 2021)
FTKMA academicians are devoted to research Exploring the unknown in wisdom universe The Dean's instruction is very loud and clear Make our faculty the innovation leader